Relationship Between Headache Characteristics and a Remote History of TBI in Veterans: A 10-Year Retrospective Chart Review. (12th July 2022) - Coffman, Colt; Reyes, Deborah; Hess, Mary Catherine; Giakas, Alec M.; Thiam, Melinda; Sico, Jason Jonathon; Seng, Elizabeth; Renthal, William; Rhoades, Charles; Cai, Guoshuai; Androulakis, X. Michelle
Abstract : Background and Objectives: The objective of this work was to examine the association between deployment-related traumatic brain injury (TBI) severity, frequency, and other injury characteristics with headache outcomes in veterans evaluated at a Veterans Administration (VA) polytrauma support clinic. Methods: We conducted a retrospective chart review of 594 comprehensive TBI evaluations between 2011 and 2021. Diagnostic criteria were based on the Department of Defense/VA Consensus-Based Classification of Closed TBI. Adjusted odds ratios (AORs) and 95% CIs were estimated for headache prevalence (logistic), headache severity (ordinal), and prevalence of migraine-like features (logistic) with multiple regression analysis. Regression models were adjusted for age, sex, race/ethnicity, time since injury, and mental health diagnoses. Results: TBI severity groups were classified as sub concussive exposure (n = 189) and mild (n = 377), moderate (n = 28), and severe TBI (n = 0). Increased headache severity was reported in veterans with mild TBI (AOR 1.72 [95% CI 1.15, 2.57]) and moderate TBI (AOR 3.89 [1.64, 9.15]) compared to those with subconcussive exposure. A history of multiple mild TBIs was associated with more severe headache (AOR 2.47 [1.34, 4.59]) and migraine-like features (AOR 5.95 [2.55, 13.77]). No differences were observed between blast and nonblast injuries; however, greater headache severity was reported in veterans with both primary and tertiary blast effects (AOR 2.56 [1.47, 4.49]). Alteration of consciousness (AOC) and posttraumatic amnesia (PTA) >30 minutes were associated with more severe headache (AOR 3.37 [1.26, 9.17] and 5.40 [2.21, 13.42], respectively). The length of time between the onset of last TBI and the TBI evaluation was associated with headache severity (AOR 1.09 [1.02, 1.17]) and prevalence of migraine-like features (AOR 1.27 [1.15, 1.40]). Last, helmet use was associated with less severe headache (AOR 0.42 [0.23, 0.75]) and lower odds of migraine-like features (AOR 0.45 [0.21, 0.98]). Discussion: Our data support the notion of a dose-response relationship between TBI severity and headache outcomes. A history of multiple mild TBIs and longer duration of AOC and PTA are unique risk factors for poor headache outcomes in veterans. Furthermore, this study sheds light on the poor headache outcomes associated with subconcussive exposure. Past TBI characteristics should be considered when developing headache management plans for veterans.